Anatomical UV Exposure in French Outdoor Workers. Issue 11 (November 2015) - Vernez, David; Koechlin, Alice; Milon, Antoine; Boniol, Magali; Valentini, Faustine; Chignol, Marie-Christine; Dore, Jean-Francois; Bulliard, Jean-Luc; Boniol, Mathieu
Abstract : Background: Solar ultraviolet has been recognized as the main causative factor for skin cancer and is currently classified as a carcinogenic agent by International Agency for Research on Cancer. Method: Results from a previous phone survey conducted in 2012 in France were used to assess exposure conditions to sun among outdoor workers. Satellite data were used in combination with an exposure model to assess anatomical exposure. Result: The yearly median exposure of the outdoor worker population is 77 kJ/m 2 to 116 kJ/m 2 . Road workers, building workers, and gardeners are the more exposed. About 70% of the yearly dose estimate is due to the cumulative summer and spring exposures. Conclusions: This study highlights the role of individual factors in anatomical exposure and ranks the most exposed body parts and outdoor occupations. Prevention messages should put emphasis on spring exposure, which is an important contributor to the yearly dose. Abstract : Supplemental Digital Content is available in the text